MANAGEMENT IN FOOTBALL CLUBS: OBTAINING THE CERTIFICADO DE CLUBE FORMADOR IN BOTAFOGO FUTEBOL CLUBE OF RIBEIRAO PRETO/SP - Lucente, Adriano dos Reis; Ruiz Bressan, Pedro Ernesto [UNESP] (Univ Nove Julho, 2018)
The most important changes in Brazilian football in recent decades, are related to the professionalization, until then a very relevant issue in the management of these clubs. One of the actions taken was to direct efforts and investments to young categories, which did not have regulations to guarantee the financial viability relative to the return on these investments. This gap was, in a way, filled with the creation of the Certificado de Clube Formador evidencing the financial importance and the potential profitability of the players trained in the youth present to their respective clubs. The main objectives of this study were to analyze and characterize the achievement of Certificado de Clube Formador for Botafogo Futebol Clube of Ribeirao Preto/SP, through a qualitative research in the form of case study, since to analyze management aspects for athletes training in football clubs is indispensable knowledge of the reality of this management, by working with subjective opinions in the generation of objective information. The results showed that the achievement of Certificado de Clube Formador for Botafogo Futebol Clube allowed the club to fit into a model of management and organization structure, thus improving its visibility in the football scenario, not being necessary for this, capital investments.
Keywords: Football clubs; Sports management; Formation athletes